Analisis Lagu "Selamat Ulang Tahun" Karya Jamrud - Robby Gautama; Yos Sudarman (SENDRATASIK UNP, 2022)
The purpose of this study was to describe the song Happy Birthday by analyzing the form and relationship of the musical elements contained in it. This study used a qualitative type of research with a content analysis approach. The research instrument used was in the form of song analysis notes, literature study, song literacy on the internet, and re-transcription of songs that the researchers did themselves. The technique of data analysis is to dissect each of the musical elements in the song separately, see the role of each element in each other, and how the musical elements are recombined in an interrelated relationship. made with a time signature of 4/4 using the basic note on the A Major scale and with a tempo of MM = 120 or 120 beats per minute, is a song that begins with the 3 beat opmat technique before entering the first beat in the initial barometer of the song. With all the elements that have been notated and analyzed, this causes the use of motifs and tones in the melody and chord accompaniment, including a simple type. When the melody of the song combines with the text that is straightforward and firm, there is an impression that the song is quite simple but more masculine. With the combination of melody and harmony in the text, with the firmness of the lyrics, this song is easily accepted by music listeners of all ages and backgrounds. So that researchers can prove that the use of musical elements in the song is closely related to the popular Happy Birthday song in the community.